High prevalence of elevated haemoglobin A1C among adolescent blood donors: Results from a voluntary screening programme including 31, 546 adolescents. (July 2015) - Gore, M Odette; Eason, Stephen J; Ayers, Colby R; Turer, Aslan T; Khera, Amit; de Lemos, James A; McGuire, Darren K; Sayers, Merlyn
More than 1 in 10 US adolescents have prediabetes or diabetes, and elevated glycosylated haemoglobin (HbA1C) in youth is associated with increased risk of death before the age of 55 years. We conducted a prospective, cross-sectional study of 31, 546 consecutive volunteer blood donors, 16–19 years of age, who donated blood during school blood drives between 1 September 2011 and 21 December 2012 in Texas. In the overall cohort, the prevalence of elevated HbA1C was 11.5%, including 11.0% in the prediabetes range (HbA1C 5.7%–6.4%) and 0.5% in the diabetes range (HbA1C ⩾ 6.5%). The prevalence of elevated HbA1C was higher in boys compared with girls (15.7% vs 7.9%, p < 0.001) and was especially high in racial/ethnic minorities (Blacks 32.7%, Asians 19.7%, Hispanics 13.1%) compared with Whites (8.0%, p < 0.001). There was a significant increase in total cholesterol and blood pressure across categories of increasing HbA1C in the overall cohort and stratified by sex and race/ethnicity. Blood donation programmes can serve as unique portals for health screening with potential for intervention in adolescents.